2021
DOI: 10.1002/agj2.20629
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitrogen application strategy and planting density optimization on sorghum yield and quality

Abstract: Nitrogen and planting density are two key factors affecting sorghum [Sorghum bicolor (L.) Moench] yield. In this study, two dwarf sorghum cultivars were used to analyze the effects of nitrogen and planting density on the yield and quality of sorghum in northern China. The experiment adopted a two-factor, split-zone design with the main plots assigned to three nitrogen application strategies, including all nitrogen applied at the sowing stage (N1), one-third nitrogen applied at the sowing stage and two-thirds n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In the study of proso millet, under the condition of nitrogen deficiency, the photosynthetic capacity and chlorophyll content of millet leaves were reduced, resulting in significantly reduced grain yield [ 49 ]. In addition, compared with other treatments, the net photosynthetic rate and chlorophyll content of sorghum leaves were significantly increased by applying nitrogen fertilizer at the jointing stage, and the yield was improved [ 50 ]. In buckwheat, the photosynthetic capacity, starch synthesis and grain yield of Tartary buckwheat were improved by nitrogen fertilizer treatment [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the study of proso millet, under the condition of nitrogen deficiency, the photosynthetic capacity and chlorophyll content of millet leaves were reduced, resulting in significantly reduced grain yield [ 49 ]. In addition, compared with other treatments, the net photosynthetic rate and chlorophyll content of sorghum leaves were significantly increased by applying nitrogen fertilizer at the jointing stage, and the yield was improved [ 50 ]. In buckwheat, the photosynthetic capacity, starch synthesis and grain yield of Tartary buckwheat were improved by nitrogen fertilizer treatment [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Optimal fertilizer rates for maximum yield have been previously documented (Mahama et al., 2014) but are typically considered on the traditional practice of complete N fertilization at planting, or even earlier. Theoretically, the split application of N at key growth stages at which plants take up N at high rates will increase yield and quality while reducing N losses (Yang et al., 2021). Grain yield varied significantly ( p < 0.01) between N treatments in environments 2 and 3 with low soil mineral N (Table S5), whereas a high soil mineral N of 95 kg N ha −1 provided enough N for plant uptake and masked the effect of N treatments on grain yield.…”
Section: Discussionmentioning
confidence: 99%
“…Presently, the plant density of grain sorghum in the spring-sown early-maturing zone is between 200,000 and 300,000 plants ha -1 , which is the largest sorghum plant density in China. Moreover, Yang et al (2021) showed that a planting density of 300,000 plants ha -1 could constitute a suitable production density to balance the individual plant photosynthetic level and sorghum yield in this region. Nevertheless, the optimum plant density depended largely on sorghum variety, growing conditions, and management practices.…”
Section: Introductionmentioning
confidence: 99%